2022
DOI: 10.3390/diagnostics12020346
|View full text |Cite
|
Sign up to set email alerts
|

Resource Management through Artificial Intelligence in Screening Programs—Key for the Successful Elimination of Hepatitis C

Abstract: Background: The elimination of the Hepatitis C virus (HCV) will only be possible if rapid and efficient actions are taken. Artificial neural networks (ANNs) are computing systems based on the topology of the biological brain, containing connected artificial neurons that can be tasked with solving medical problems. Aim: We expanded the previously presented HCV micro-elimination project started in September 2020 that aimed to identify HCV infection through coordinated screening in asymptomatic populations and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…The AI/ML applications introduced in this review showed comparable or better performance to the traditional third‐generation rapid HCV‐Ab tests 64,91 . The only outlier was the ML model by Butaru 40 , which had a very low predictive power for detecting positive HCV infections. However, it performed similarly to rapid HCV‐Ab as a Point‐of‐Care (POC) tool to exclude HCV infection (Table 2).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The AI/ML applications introduced in this review showed comparable or better performance to the traditional third‐generation rapid HCV‐Ab tests 64,91 . The only outlier was the ML model by Butaru 40 , which had a very low predictive power for detecting positive HCV infections. However, it performed similarly to rapid HCV‐Ab as a Point‐of‐Care (POC) tool to exclude HCV infection (Table 2).…”
Section: Discussionmentioning
confidence: 91%
“…Wei, L. & Ying, X., 2011 34 ; Wang, M. et al, 2012 35 ; Wei, Y. et al, 2016 36 ; Malik, A. A. et al, 2021 37 ; Wei, Y. et al, 2019 38 ; Reiser, M. et al, 2019 39 ; Butaru, A. E. et al, 2022 40 ; Villarreal, Y. R. et al, 2019 41 ; Doyle O. M. et al, 2020 42 ; Edeh, M. O. et al, 2022 43 ; Chirikov, V. V. et al, 2018 44 ; Park, H. et al, 2022 45 ; Janczewska, E. et al, 2021 46 ; Haga, H. et al, 2020 47 ; Churkin, A. et al, 2022 48 ; Rivero‐Juárez, A. et al, 2020 49 ; Oselio, B. et al, 2022 50 ; Weber, T. et al, 2022 51 ; Itami‐Matsumoto et al, 2019 52 ; Hashem, S. et al, 2020 53 ; Audureau, E. et al, 2020 54 ; G. Wong et al, 2022 55 ; Hershberger, C. E. et al, 2021 56 …”
Section: Discussionunclassified
See 2 more Smart Citations
“…Therefore, random samples from each class in the dataset were duplicated. This technique has been proven to be effective when dealing with class imbalance [ 14 , 15 ]. The dataset was split in 70% samples for training and 30% samples for validation.…”
Section: Proposed Methodsmentioning
confidence: 99%